Removal of Fluoride from Aqueous Media by Zirconium Modified Zeolite - Zhou1, Hui; Chen1, Wen; Yue Gao1, Zhi; Chen2, Dong (Asian Journal of Chemistry, 2014)
In this study, the fluoride adsorption potential of novel zirconium modified zeolite composite was explored. Batch adsorption experiments were conducted to study and optimize various operational parameters, such as adsorbent dose, contact time, pH, temperature and initial fluoride concentration. It was observed that the zirconium modified zeolite work effectively in neutral solution and showed a maximum adsorption rate of 97.62 % at an initial fluoride concentration of 10 μg/mL, it is much better than raw zeolite of 32.94 % and acid modified zeolite of 57.05 %. The experimental data fitted well into Freundlich adsorption isotherm and follows pseudo-second-order kinetics. Thermodynamic study suggests that fluoride adsorption on zirconium modified zeolite is reasonably spontaneous and an endothermic process. The nature and morphology of sorbents was characterized by using XRD, BET and SEM analysis. From the experimental results, it may be inferred that chemical modification enhances the fluoride removal efficiency of raw zeolite and zirconium modified zeolite works as an effective adsorbent for defluoridation of water.